Jean Baudrillard - Lane, Richard J. (Routledge, 2000)
Best known as the philosopher who claimed that the Gulf War never happened, Jean Baudrillard is one of the most famous and controversial writers on postmodernism. This book offers a beginners guide to his thought, including his views on: * technology * primitivism * reworking Marxism * simulation and hyperreality * America and postmodernism. Richard Lane places Baudrillard's key ideas in the context of French and postmodern thought and examines the ongoing impact of his work. Concluding with an extensively annotated bibliography of the original texts, this is the perfect companion for any student approaching the work of Jean Baudrillard.